The influence of household environment on caregivers' overload of children with cerebral paralysis = A influência do ambiente domiciliar na sobrecarga de cuidadores de crianças com paralisia cerebral - Alessandra Alcides de Sá Santos; Jamille Alves Araújo; Marlizete Maldonado Vargas; Cristiane Costa da Cunha Oliveira (Universidade Estadual de Maringá, 2012)
The environment is considered an extremely important factor in individuals' health promotion and life quality. The influence that the environment exerts on caregivers' lives is due to all the complications they have to experience. Current study investigates the influence of family environment on the overload of caregivers of children with cerebral paralysis. The research comprised 21 caregivers, whose overload intensity was assessed by three instruments: a caretaker characterization form, Zarit Caregiver Burden Interview (ZBI) and an environmental characterization protocol. Results showed that all caregivers revealed a certain level of overload (52.4% intense and 47.6% moderate). Physical modifications were observed in 52.4% of the residences under survey but none was undertaken by a professional in rehabilitation. A statistically significant correlation occurred in children's spatial movement (p=0.031). Research suggests that caregivers of children with cerebral paralysis are overburdened due to the health care activities and that the environment constitutes a risk factor. O ambiente é considerado fator de extrema importância na promoção de saúde e qualidade de vida dos indivíduos. Determinar a influência que o ambiente exerce na vida de cuidadores surge como uma necessidade diante de todas as dificuldades por eles enfrentadas. O objetivo deste estudo foi investigar a influência do ambiente familiar na sobrecarga dos cuidadores de criança com paralisia cerebral. A pesquisa contou com 21 sujeitos, cujo nível de sobrecarga foi levantado por meio de três instrumentos, um formulário de caracterização do cuidador, o inventário de sobrecarga de Zarit e um protocolo de caracterização do ambiente. Os resultados encontrados foram que todas as cuidadoras apresentavam sobrecarga (52,4% intensa e 47,6% leve). Observou-se a existência de adaptações em 52,4% dos domicílios estudados, no entanto nenhum deles tinha sido adaptado por um profissional de reabilitação. Foi encontrada uma correlação estatisticamente significativa com a existência de espaço para criança se locomover (p = 0,031). O trabalho sugere que cuidadoras de crianças com paralisia cerebral são sobrecarregadas em decorrência da atividade de cuidar, tendo o ambiente muitas vezes como fator de risco.